Efficient propagation of variant Creutzfeldt‐Jakob disease prion protein using the cell‐protein misfolding cyclic amplification technique with samples containing plasma and heparin. Issue 1 (8th September 2015) - Oshita, Masatoshi; Yokoyama, Takashi; Takei, Yumiko; Takeuchi, Atsuko; Ironside, James W.; Kitamoto, Tetsuyuki; Morita, Masanori
Abstract : BACKGROUND: To prevent the iatrogenic spread of variant Creutzfeldt‐Jakob disease (vCJD) between humans via blood products or transfusion, highly sensitive in vitro screening tests are necessary. Protein misfolding cyclic amplification (PMCA) is one such candidate test. However, plasma has been reported to inhibit the PMCA reaction. Therefore, we investigated the cell‐PMCA conditions that permit vCJD prion amplification in the presence of plasma. STUDY DESIGN AND METHODS: Cell‐PMCA of vCJD samples was performed by adding various final concentrations of pooled plasma, citrate‐phosphate‐dextrose (CPD), albumin, globulin, or pooled plasma treated with ion exchangers. After heparin and plasma concentrations were optimized, multiround cell‐PMCA was performed. RESULTS: When 1% to 50% of pooled plasma was added to heparinized cell‐PMCA, amplification efficiency showed a double‐peaked profile at less than 1% and 40% final plasma concentrations, indicating that plasma contains not only PMCA inhibitors but also promoters. Intravenous globulin did not inhibit cell‐PMCA, but the protein G–bound fraction did. CPD, albumin‐depleted plasma, and the unbound fraction of anion‐exchange chromatography inhibited cell‐PMCA, but albumin and the unbound fraction of the cation‐exchange chromatography did not. The detection limit of abnormal prion protein in multiround cell‐PMCA, when maintaining the final plasma concentration at 40% at each round, was 10 −10 dilutions of a vCJD brain specimen. CONCLUSION: We have established a novel cell‐PMCA format in the presence of plasma without any pretreatment, where vCJD prion protein was amplified at comparable levels to that found without plasma. Our data suggest the feasibility of cell‐PMCA as a practical blood test for vCJD prions.